Spontaneous Hypothermia As an Indicator of Early Diffuse Anoxic Brain Injury in Post-Cardiac Arrest Patients - Sydney V. Palka, MD; Jenna A. Gonillo-Davis, NP; Benjamin P. George, MD, MPH; Daryl C. McHugh, MD, MPH (Critical Care Explorations, 2024)
OBJECTIVES:. To determine the association between spontaneous hypothermia (SH), defined as initial post-resuscitation core body temperature less than 34°C, and diffuse anoxic brain injury (DABI) on initial CT scan of the head (CTH) in post-cardiac arrest patients. DESIGN, SETTING, AND PARTICIPANTS:. This was a retrospective, observational cohort study. This study was performed at the University of Rochester Medical Center Strong Memorial Hospital. All in-hospital and out-of-hospital cardiac arrest patients with return of spontaneous circulation admitted between January 1, 2022, and October 31, 2022, were included. MAIN OUTCOMES AND MEASURES:. The primary outcomes were the odds of DABI on initial CTH for patients with SH compared with patients without SH post-cardiac arrest using a multivariable logistic regression controlling for patient covariates including basic demographics and arrest features. DABI on initial CTH was measured qualitatively and quantitatively using neuroradiologist interpretation and calculated gray-white matter ratio of the basal ganglia, respectively. Secondary outcome measures included length of stay (LOS), inpatient mortality, and those who underwent withdrawal of life-sustaining therapy (WOLST) or progression to brain death. RESULTS:. Out of the observed 150 cases of cardiac arrest, 31 patients (21%) had SH. Of the 128 patients who had an initial CTH performed, 27 (21%) had DABI. The adjusted odds ratio of DABI on initial CTH associated with SH was 3.55 (95% CI, 1.08–11.64; p = 0.036) and 2.18 (95% CI, 0.69–6.91; p = 0.182) when DABI was measured qualitatively and quantitatively, respectively, after controlling for multiple covariates. There was a difference observed in LOS between the groups (3 vs. 10 d; p = 0.0005) and this was driven by early WOLST. CONCLUSIONS AND REVELANCE:. Patients presenting with SH after cardiac arrest may be at greater risk of early DABI on initial CTH compared with those with higher body temperatures in the post-arrest period. Recognition of early SH may help to risk stratify post-cardiac arrest patients at highest risk of DABI.